The Role of Organizational Innovation as a Mediator Between Digital Payment Systems and Business Sustainability - Sugesti, Endah; Kusmantini, Titik; Nilmawati, Nilmawati (CV. Strata Persada Academia, 2025)
This study investigates the mediating role of organizational innovation in the relationship between digital payment systems and business sustainability among creative Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta, Indonesia. Amidst the digital transformation trend, digital payment systems such as e-wallets, QRIS, and mobile banking have become critical tools for MSMEs to enhance efficiency and expand market reach. However, the sustainability of MSMEs remains challenged by limited technological adaptation, low digital literacy, and inefficiencies in operational management. Using a quantitative descriptive approach, this study collected data from 100 purposively sampled MSMEs that had adopted digital payment technologies. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between digital payment systems, organizational innovation, and business sustainability. The results reveal that while digital payment systems exert a moderate direct effect on business sustainability, their indirect effect through organizational innovation is significantly stronger. The mediation analysis confirms that organizational innovation plays a complementary and substantial role in amplifying the impact of digitalization on long-term business performance. These findings highlight the necessity of integrating technological adoption with internal innovation strategies to achieve sustainable competitiveness. The study recommends increased institutional support to foster digital literacy and innovation capacity among MSMEs and calls for future research to explore additional mediating variables and sectoral comparisons using mixed methods.